الرؤية السريالية في رسوم ( بةختيار قةفتان ) - فخري, هاورى انور (Sulaimani Journal for Humanities, 2021)
This research concerns with examining (The Surrealism Vision in Bakhtyar Qaftan Paintings), and it consists of four chapters. The first chapter concerns with displaying the research problem, importance and objectives of the study, limitations and terminology determination. The second chapter that designed as a theoretical framework includes three topics. The first topic (The Surrealism Roots and Concept) defines (Surrealism)’s, terminology, methodology, philosophy, how it established and the effective factors, as well as its ideological references. The second topic titled; (The Surrealism in Painting) concerns with explaining the history and the emergence of the Surrealist paintings and the most distinctive global painters who have role in establishing and spreading this approach. While the third topic (The Experiment of The Artist Bakhtiar Qaftan), highlighting the life of the artist and his experiments, developments, and his arts conversions. The Third Chapter represents the (Research Methodology and Its Procedures) including, (methodology), in that the researcher has depended in analyzing the samples on (Descriptive Analysis) method, that resulted in outcomes that answered the study objective. Theses answers are displayed along with the recommendations in the fourth chapter. Some of these results are shown as follows: 1-The social and political factors that Kurdistan went through had a great influence on the content and the artistic vision of the artist. This is in addition to the psychological factors as well as the wars and revolutions that helped to turn the rich, intellectual and visual message to a creative and humanistic message, as in the samples (1),(2),(3), (4). 2-The visual message is loosen in the paintings from determining the specific meaning and the direct and logical vision in order to sublimate the pictures towards liberated imagination from realistic subjects and opening up to multiple meaning and infinite interpretations. 3-The artist contented in (3) and (4) samples within chromatics levels between blue, greenish blue gray, red and purple in order to show the harmony between the contrasting colors according to various presentation techniques, and structural geometric \ designeatal composition.